In vitro and in vivo assessment of eprociclovir as antiviral treatment against testudinid herpesvirus 3 in Hermann's tortoise (Testudo hermanni). (June 2019) - Gandar, Frédéric; Marlier, Didier; Vanderplasschen, Alain
Abstract: Tortoises belonging to the Testudinidae family are infected by Testudinid herpesviruses. Testudinid herpesvirus 3 (TeHV-3) is considered the most pathogenic and affects several tortoise species, particularly those from the Testudo genus. As most species of this genus are endangered contribute to ecological concerns over this virus. Here, we aimed to explore the rational development of an antiviral treatment against TeHV-3 using Hermann's tortoise ( Testudo hermanni ) as a host model. Ten antiviral compounds were tested in cell culture for their toxicity and their activity against TeHV-3. Eight compounds exhibited different levels of activity against TeHV-3 with either no or only minor cytotoxic effects on cells. Next, eprociclovir (EPV, ciprovir) was selected for further investigations in vivo. Its pharmacokinetic properties were investigated after a single sub-cutaneous administration at 5 or 10 mg/kg. Plasma concentrations remained above half maximal effective concentration (EC50 ) for 2.2 and 4.4 h after administration at 5 and 10 mg/kg, respectively. Finally, EPV toxicity was investigated after administration at the dose of 10 mg/kg, BID for seven consecutive days. As early as one day after initiation of the treatment up to its end, EPV plasma concentration remained under the EC50. Apathy and anorexia developed after 7 days. Biochemical and anatomopathological examinations revealed nephrotoxic effects of EPV. Altogether, these data suggest that EPV is not a suitable molecule for the treatment of TeHV-3. Further studies are required to determine whether the other molecules identified here for their anti-TeHV-3 activity represent potential candidates for the development of efficacious treatments. Highlights: Assessment of eprociclovir (EPV, previously known as ciprovir) as antiviral treatment against testudinid herpesvirus 3 in Testudo hermanni EPV pharmacokinetics and its toxicity do not support its use for the treatment against testudinid herpesvirus 3 in tortoise